Causal relationship between genetically predicted uterine leiomyoma and cancer risk: a two-sample Mendelian randomization - Zhao, Chenyang; Shang, Anquan; Wu, Han; Li, Qiong; Peng, Lixiu; Yue, Chaoyan (Frontiers in Endocrinology, 2024)
Purpose: Studies have demonstrated that hormonal imbalance, including increased estrogen or decreased progesterone were the main inducing factor of uterine leiomyoma (UL) development and some cancers. UL has been reported to be ralated with several cancers in observational studies.However, the casual assocciations between UL and cancers remain unclear.We conducted a two-sample Mendelian randomization (MR) analysis to investigate the casual assocciations between UL and 16 site-specific cancers using the public databases. Four methods were applied in our MR analysis, including the inverse variance weighting (IVW), MR-Egger, weighted median and weighted mode. We also performed sensitivity tests to evaluate the robustness of the causal assocciations.Results: IVW analysis showed that genetically predicted uterine leiomyoma were associated with high risk of low malignant potential ovarian cancer (OR = 1.22, 95% CI: 1.06-1.40, p = 0.004), serous